Empirical analysis of collateral at central counterparties - Magdalena Grothe; N. Aaron Pancost; Stathis Tompaidis (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
This paper studies the risk management of central counterparties (CCPs) using a granular transaction-level dataset. We test whether margining practices are sufficient relative to portfolio risk and whether CCPs reduce margin requirements in a "race-to-the-bottom." We find that, for some CCPs, margin breaches are predictable ex ante, but the portfolios of more interconnected clearing members are associated with higher margin holdings. While margin requirements increased significantly around the onset of the Covid-19 pandemic, controlling for portfolio and macro-financial variables, margin breaches did not. Our results indicate that changes in margins should be analyzed alongside margin breaches.
Keywords: G23; G21; G15; 330; CCP; risk management; initial margin; variation margin